PENINGKATAN HASIL BELAJAR BANGUN DATAR MELALUI MODEL DISCOVERY LEARNING BERBANTUAN CANVA PADA PESERTA DIDIK KELAS IV SDN 21 PARAK KOPI - Meilani Hasibuan, Syakinah; Salmaini Safitri Syam; Yullys Helsa; Salmaini Syofyan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low mathematics learning outcomes of grade IV students at SDN 21 Parak Kopi on two-dimensional figures, with an initial completeness rate of only 16% (class average 55) and a teacher-centered learning process. This study aims to describe the improvement of student learning outcomes on two-dimensional figures through the application of the Canva-assisted Discovery Learning model. The method used is Classroom Action Research (CAR) with a mixed-methods approach (qualitative and quantitative) carried out in two cycles following the Kemmis & McTaggart flow. The research subjects consisted of 25 grade IV students. Data were collected through observation, interviews, documentation, and tests. The results showed a significant overall improvement. The implementation of teacher and student activities increased to 96.8% (Excellent) in cycle II meeting II. Learning outcomes in the knowledge domain increased from an average of 73.72 in cycle I to 91.2 in cycle II, where 22 students successfully achieved the passing grade. The skill domain also increased from an average of 79.32 to 89.33, and the average attitude assessment reached 89.58% at the end of cycle II. It is concluded that the implementation of the Canva-assisted Discovery Learning model is highly effective in improving students' mathematics activities and learning outcomes.